Musik Noise: Sebuah Seni, Ekspresi, dan Perlawanan - Dwi Setyo Utomo (Umbara, 2018)
Noise is a type of music that is played by using instruments to produce loud. Unlike music in general, which presents harmonization of tones to enjoy its beauty, noise music presents noise to be enjoyed. This study explores and describes noise music in Bandung, as a performing art as well as a symbolic expression of the musicians and their audiences. This study uses a qualitative approach with ethnographic methods, and data collection techniques through observation, interviews and literature studies. This research found that noise music is an alternative which is also a symbolic expression of the musicians. They express their emotions and opinions through the noise created by various tools. The creation of noise and the use of musical instruments in combination with objects that are not musical instruments (for example, loudspeakers, and washbasins) are a symbol of breaking the standard of general musical art which tends to present aesthetics and order.